2021
DOI: 10.1002/ange.202110653
|View full text |Cite
|
Sign up to set email alerts
|

An Overlooked Natural Hydrogen Evolution Pathway: Ni2+ Boosting H2O Reduction by Fe(OH)2 Oxidation during Low‐Temperature Serpentinization

Abstract: Natural hydrogen (H 2 ) has gained considerable attentions as a renewable energy resource to mitigate the globally increasing environmental concerns. Low-temperature serpentinization (< 200 8C) as a typical water-rock reaction is a major source of the natural H 2 . However, the reaction mechanism and the controlling step to product H 2 remained unclear, which hinders the further utilization of natural H 2 . Herein, we demonstrated that the H 2 production rate could be determined by the Fe(OH) 2 oxidation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In our previous study, we found that pure Fe(OH) 2 suspensions can indeed produce H 2 during heating (50-90 °C), but the yield is extremely limited. 18 At the same time, we also found that coprecipitated Ni 2+ can significantly improve the capacity of Fe(OH) 2 suspensions to produce H 2 , when the OH − content in the solution was inadequate, with the generation of magnetite from 50 °C to 90 °C. Then, by means of isotope experiments and the H 2 O-Fe(OH) 2 surface reaction according to eqn (4), we reasonably explained the promotion role of coprecipitated Ni 2+ and inhibition role of OH − on H 2 O reduction at the Fe(OH) 2 surface.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…In our previous study, we found that pure Fe(OH) 2 suspensions can indeed produce H 2 during heating (50-90 °C), but the yield is extremely limited. 18 At the same time, we also found that coprecipitated Ni 2+ can significantly improve the capacity of Fe(OH) 2 suspensions to produce H 2 , when the OH − content in the solution was inadequate, with the generation of magnetite from 50 °C to 90 °C. Then, by means of isotope experiments and the H 2 O-Fe(OH) 2 surface reaction according to eqn (4), we reasonably explained the promotion role of coprecipitated Ni 2+ and inhibition role of OH − on H 2 O reduction at the Fe(OH) 2 surface.…”
Section: Introductionmentioning
confidence: 59%
“…Fe(OH) 2 was crafted according to our previous work. 18 5 mL of 0.04 M FeCl 2 solution and 4.6 mL of deoxygenated water were added to a 50 mL quartz reactor, and then the reactor was immediately sealed. After air extraction and ventilation with argon (99.9999%) repeatedly 3 times, 0.4 mL 1 M NaOH was injected into the reactor using a micro syringe.…”
Section: Synthesis Of Fe(oh)mentioning
confidence: 99%
See 3 more Smart Citations